Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/pharmaceutics12080746
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability in the Older Population: The Importance of an Appropriate Tablet Size

Abstract: Presenting many advantages, solid oral dosage forms (SODFs) are widely manufactured and frequently prescribed in older populations regardless of the specific characteristics of patients. Commonly, patients with dysphagia (swallowing disorders) experience difficulties taking SODFs, which may lead to non-adherence or misuse. SODF characteristics (e.g., size, shape, thickness) are likely to influence swallowability. Herein, we used the acceptability reference framework (the ClinSearch acceptability score test (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 25 publications
(30 reference statements)
0
25
0
Order By: Relevance
“…There is a consensus that the size, shape, color, taste, and mouthfeel have a significant impact on drug product swallowability and acceptance. In order to achieve good compliance, as well as effective, safe, and independent pharmacotherapy, it is important for physicians and pharmaceutical professionals to be informed regarding potential problems that are related to a patient’s inability to swallow SODF, in order to prescribe/dispense suitable drug formulations and/or designs that can better meet the specific needs of each patient [ 26 , 32 , 121 , 207 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a consensus that the size, shape, color, taste, and mouthfeel have a significant impact on drug product swallowability and acceptance. In order to achieve good compliance, as well as effective, safe, and independent pharmacotherapy, it is important for physicians and pharmaceutical professionals to be informed regarding potential problems that are related to a patient’s inability to swallow SODF, in order to prescribe/dispense suitable drug formulations and/or designs that can better meet the specific needs of each patient [ 26 , 32 , 121 , 207 ].…”
Section: Discussionmentioning
confidence: 99%
“…A usual approach for increasing patient compliance and reducing pill burden is done by increasing the SODF size in order to accommodate a higher dose strength [ 104 ]. This rule does not apply to older patients, as these perceive SODF as being more difficult to swallow with increasing size and consider the size of the SODF to be the most important physical attribute for swallowing safety [ 26 , 100 , 102 ]. This is supported by a study that identified a correlation between higher esophageal muscle effort with an increasing size of the SODF to be administered.…”
Section: Administration Of Sodf By Older Patientsmentioning
confidence: 99%
See 3 more Smart Citations